Co może być największym zagrożeniem dla polszczyzny następnych pokoleń? Jak przeciwstawiać się deprecjacji języka polskiego? - Cieślikowa, Aleksandra (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
With regard to the issues discussed during the debate on The Polish Language of Four Generations that took place on 21st February 2012 in the Presidential Residence, the author tries to indicate the problems that the Commission for Names of Places and Physiographic Objects keeps facing in their works (proper names found in the belles-lettres are also prone to depreciation). The main problems result from the willingness to acquiesce traditional usage with the rules of standard Polish. The lack of financial subsidy for the work of the members of the Commission has a negative effect on the preparation of the next issue of the Official List of Place Names in Poland.